Biodiversity and Litter Breakdown in a Karstic Freshwater System (Doberdò Lake, Northeast Italy) in Relation to Water Level Fluctuations and Environmental Features - Marco Bertoli; Davide Lesa; Alessia Merson; Paolo Pastorino; Marino Prearo; Elisabetta Pizzul (Diversity, 2022)
The present study reports seasonal data about chemico-physical trends, macrobenthic invertebrates, and Phragmites australis decomposition rates within a karstic freshwater system in the western classic Karst. Results presented herein were compared with those obtained from the same system five years ago. Chemico-physical data showed higher temperatures and lower levels of pH and conductivity than in the past. The macrobenthic invertebrate community varied through the seasons and through the years, though they are dominated by few taxa, such as Asellus and Gammarus. These shredders were the most abundant functional feeding guild, playing a pivotal role in the decomposition of the vegetal organic matter. Decomposition rates k ranged between 0.009 and 0.016 days−1 and varied seasonally. k values were different from those previously reported for the investigated system. Differences are mainly due to changes in water supply, depending on decreasing rainfall regimes and hydrometric levels of the Soča River, which showed lower levels than in the previous study. Changes in water supply altered the fluctuating pulse that is typical of ephemeral karstic lakes, changing the system dynamics. Potential effects of climate change on local scale are also discussed.